2017
DOI: 10.18433/j32p6r
|View full text |Cite
|
Sign up to set email alerts
|

A Short Guide to Electrophysiology and Ion Channels

Abstract: ABSTRACT:The birth and discovery of electrophysiological science took place in the 18 th century laying the path for our understanding of nerve membrane ionic currents. The pore-forming proteins, ion channels, are involved and play critical roles in very important physiological and pathological processes, such as neuronal signaling and cardiac excitability, therefore, they serve as therapeutic drug targets. The study of physiological, pharmacological and biophysical properties of ion channels can be done by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 122 publications
0
40
0
Order By: Relevance
“…Ion channels are pore‐forming proteins, which are involved and play critical roles in very important physiological and pathological processes, such as neuronal signalling and cardiac excitability. Therefore, ion channels serve as therapeutic drug targets (Bagal et al, ; Rubaiy, ). The human transient receptor potential (TRP) proteins comprise a family of 27 cation channels that are predominately calcium (Ca 2+ )‐permeable (Nilius & Szallasi, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ion channels are pore‐forming proteins, which are involved and play critical roles in very important physiological and pathological processes, such as neuronal signalling and cardiac excitability. Therefore, ion channels serve as therapeutic drug targets (Bagal et al, ; Rubaiy, ). The human transient receptor potential (TRP) proteins comprise a family of 27 cation channels that are predominately calcium (Ca 2+ )‐permeable (Nilius & Szallasi, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the function of TRPC1 is a matter of debate, as when expressed alone, it does not form a functional ion channel (Beech, ; Rubaiy, Ludlow, Henrot, et al, ). For the past two decades, a plethora of studies have reported that the TRPC channels play vital roles in many physiological and pathological mechanisms (Beech, ; Nilius & Szallasi, ; Rubaiy, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transient receptor potential canonical (TRPC) proteins are a subfamily of the TRP superfamily and assemble as homo and heterotetramers to form Ca 2+ ‐permeable non‐selective cationic channels (Abramowitz and Birnbaumer, ; Beech, ; Damann et al ., ; Gaunt et al ., ; Moran et al ., ; Rubaiy, ). They appear to function in two clusters, TRPC1 / TRPC4 / TRPC5 and TRPC3/TRPC6/TRPC7, which are distinguishable pharmacologically (Akbulut et al ., ; Bon and Beech, ; Maier et al ., ; Miller et al ., ; Washburn et al ., ; Rubaiy et al ., ,b).…”
Section: Introductionmentioning
confidence: 98%